Smarter Dosing for the Tiniest Patients: AI in Neonatal Pharmacology - M J, Manjula; S, Bhavya; M J, Swetha (Journal of Neonatal Surgery, 2025)
Artificial Intelligence (AI) is revolutionizing healthcare, particularly in precision medicine and clinical decision-making. In neonatal care, accurate dosing of the drugs, fluids, in case of surgeries, the required anesthetics and analgesics is critical for patient safety and outcomes. This review explores the current landscape of AI-based dosage algorithms used in intraoperative and postoperative neonatal care, evaluating their development, application, performance, and clinical integration. We discuss role of machine learning models, data sources, algorithmic transparency, and ethical considerations, challenges and future directions in neonatal care with special emphasize of surgical and intensive care.